PTU-113 Hepcidin does not predict response to iron therapy in pre-operative anaemia in patients with colorectal cancer. (17th June 2017) - Ng, O; Keeler, BD; Simpson, JA; Al-Hassi, HO; Acheson, AG; Brookes, MJ
Abstract : Introduction: Hepcidin has a key role in systemic iron homeostasis. We assessed if serum hepcidin predicts response to either intravenous or oral iron therapy in the treatment of pre-operative anaemia. Method: As part of the IVICA trial [1], patients with iron-deficiency anaemia undergoing elective surgery for colorectal cancer were randomised to receive oral ferrous sulphate (n=58) or intravenous Ferinject (n=54) for a minimum of two weeks before surgery. Blood samples were taken at recruitment (prior to iron therapy) and on the day of surgery (after iron therapy). Clinical data was collected prospectively. Changes in haemoglobin from recruitment to day of surgery were measured. Serum were analysed using an ELISA assay to determine hepcidin levels. Association between hepcidin levels and mean haemoglobin change from recruitment to day of surgery were tested using the Mann Whitney U test. High hepcidin was defined as >56 ng/ml. Results: Both oral and intravenous iron groups were similar at baseline for recruitment haemoglobin (9.9 g/dL and 9.6 g/dL respectively, p=0.2). Median hepcidin levels were 1.9 ng/mL (range 0–86) in the oral iron group and 1.7 ng/mL (range 0–205 ng/mL) in the IV iron group. No correlation was found between hepcidin levels and haemoglobin change in either oral or intravenous groups. Mean haemoglobin change was similar for those with high hepcidin levels (1.14 g/dL) compared to low hepcidin levels (1.12 g/dL) with no statistical difference found (p=0.949). Subset analysis of oral and intravenous groups also showed no differences (p=0.679 and p=0.775 respectively). Conclusion: In this study, neither absolute hepcidin nor high hepcidin levels>56 ng/ml predicted response to iron therapy, irrespective of the route of administration of iron therapy. Reference: . Keeler BD, et al. Randomised clinical trial of preoperative oral versus intravenous iron in anaemic patients with colorectal cancer. Br J Surg, 2017;104(3):214–221. Disclosure of Interest: None Declared